2018
DOI: 10.1002/mnfr.201700842
|View full text |Cite
|
Sign up to set email alerts
|

Lipid‐Modifying Effects of Chitosan Supplementation in Humans: A Pooled Analysis with Trial Sequential Analysis

Abstract: Supplementation with chitosan effectively reduces plasma concentrations of TC and LDL-C. Current evidence indicates daily chitosan supplementation as a candidate for therapeutic lipid management strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Thus, the present study had enlarged sample sizes and added statistical power of at least 1600 cases. Second, to explore whether the current evidence was reliable and conclusive, and to prevent repeated updates from increasing the risk of random errors, we further applied TSA to evaluate the effects of repetitive testing, which increased the robustness of our findings ( Huang et al., 2018 ; Huang et al., 2020 ). Third, we rated the quality of evidence using GRADE approach with the guidance of an experienced GRADE methodological expert.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the present study had enlarged sample sizes and added statistical power of at least 1600 cases. Second, to explore whether the current evidence was reliable and conclusive, and to prevent repeated updates from increasing the risk of random errors, we further applied TSA to evaluate the effects of repetitive testing, which increased the robustness of our findings ( Huang et al., 2018 ; Huang et al., 2020 ). Third, we rated the quality of evidence using GRADE approach with the guidance of an experienced GRADE methodological expert.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to previous studies, our study has several advantages. First, only two meta-analyses of chitosan have been performed, which evaluated body weight and lipid modification [ 25 , 70 ]. This is the first meta-analysis to evaluate regulation of the glycemic index following supplementation with chitosan, making it the latest and most comprehensive study to date.…”
Section: Discussionmentioning
confidence: 99%
“…As a deacetylated form of chitin, chitosan is an important dietary fiber source and among the most abundant natural polysaccharides worldwide [19], as it is derived from numerous taxa, including crustacean shells, insect exoskeletons, parasitic nematode eggs and gut linings, and fungi cell walls [20]. Chitosan is generally considered as a non-toxic nutritional cellulose supplement [21], and several animal studies and human clinical trials have demonstrated its good health effects, such as the prevention of cancer, hypertension, hyperglycemia, diabetes, dyslipidemia, and inflammation [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Although several clinical trials studied the efficacy of chitosan, the benefits of chitosan and its derivatives on glycemic regulation are not conclusive, due to these clinical trials varying substantially regarding the design of clinical research, the dosage, and the duration of chitosan supplementation, and characteristics of the enrolled population. Notably, a pooled analysis with trial sequential analysis showed that supplementation with chitosan effectively reduced plasma TC and LDL-C levels, indicating that daily chitosan consumption might be a worthwhile dietary approach to prevent hypercholesterolemia [105]. A meta-analysis of randomized controlled trials further showed that body weight, body mass index (BMI) and body fat were significantly reduced by chitosan supplementation, particularly in obese and overweight individuals [106].…”
Section: Application Of Chitosan and Its Derivatives In Clinical Trialsmentioning
confidence: 99%